2000
DOI: 10.1110/ps.9.10.1866
|View full text |Cite
|
Sign up to set email alerts
|

Exchanging the active site between phytases for altering the functional properties of the enzyme

Abstract: By using a novel consensus approach, we have previously managed to generate a fully synthetic phytase, consensus phytase-1, that was 15-26 8C more thermostable than the parent fungal phytases used in its design~Lehmann et al., 2000!. We now sought to use the backbone of consensus phytase-1 and to modify its catalytic properties. This was done by replacing a considerable part of the active site~i.e., all the divergent residues! with the corresponding residues of Aspergillus niger NRRL 3135 phytase, which displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 30 publications
2
11
0
1
Order By: Relevance
“…4C). A similar shift in pH optimum with the K68A mutation and with phytic acid as a substrate was also seen for the A. fumigatus Q27I variant and for several consensus phytases (consensus phytase-1 Q27T, consensus phytase-1 thermo [8] Q27T, and consensus phytase-10 thermo[3] Q27T; Fig. 4B and data not shown; for a detailed description of the different consensus phytases, see references 7 and 9 and M. Lehmann, C. Loch, A. Middendorf, D. Studer, S. F. Lassen, L. Pasamontes, A. P. G. M. van Loon, and M. Wyss, unpublished data).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…4C). A similar shift in pH optimum with the K68A mutation and with phytic acid as a substrate was also seen for the A. fumigatus Q27I variant and for several consensus phytases (consensus phytase-1 Q27T, consensus phytase-1 thermo [8] Q27T, and consensus phytase-10 thermo[3] Q27T; Fig. 4B and data not shown; for a detailed description of the different consensus phytases, see references 7 and 9 and M. Lehmann, C. Loch, A. Middendorf, D. Studer, S. F. Lassen, L. Pasamontes, A. P. G. M. van Loon, and M. Wyss, unpublished data).…”
Section: Resultssupporting
confidence: 63%
“…In addition, we have determined the crystal structure of A. niger phytase at a 2.5-Å resolution (4). Inspection of this three-dimensional (3D) structure, comparison with other high-M r histidine acid phosphatases, and site-directed mutagenesis of residues in the presumed active site (8,25,25) yielded strong evidence for a highly positively charged cleft at the interface between the smaller ␣-domain and the larger ␣/␤-domain of the molecule as the substrate binding (active) site.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al also discussed the role of noncovalent intramolecular interactions in the thermostability of barnase [19]. Some experimental studies have reported that phytase thermostability was enhanced using various methods, including the introduction of a consensus sequence [20,21], rational design [16,22], directed evolution [23,24], and the introduction of hydrogen bonds or ionic interactions [13,17]. Using MD simulation, numerous sites and regions in many proteins have been recognized as enhancing thermal stability [17,[25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…1). Consensus-7 phytase (Lehmann et al, 2000b), produced by substitution of the active site of Anp for its counterpart in consensus-1 phytase (Lehmann et al, 2000a), exhibits a major, although not complete, shift in pH-activity profile towards Anp, and a much greater T m (70.4 • C). Despite the same active site shared by Anp, chimera ABCDEFG, and consensus-7 phytase, Anp possesses the highest level of specific activity.…”
Section: Discussionmentioning
confidence: 99%
“…Many positions influencing the catalytic properties of Anp or Afp have been identified by site-directed mutagenesis on the basis of 3D structure and sequence alignment (Wyss et al, 1999b;Tomschy et al, 2000aTomschy et al, ,b, 2002Mullaney et al, 2002;Kim et al, 2006;Zhang and Lei, 2008). All these positions are located within the theoretical catalytic pocket (Lehmann et al, 2000b). Among them, however, only positions E205, K277 and H282 (all positions are numbered according to the amino acid numbering of mature Anp (Kostrewa et al, 1997) on the basis of sequence alignment) are responsible for the differences in substrate specificity and activity in the acidic pH range between Anp and Afp (Tomschy et al, 2002;Mullaney et al, 2002;Kim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%